A novel QTL on chromosome 5AL of Yangmai 158 increases resistance to Fusarium head blight in wheat. (22nd December 2019) - Jiang, P.; Zhang, X.; Wu, L.; He, Y.; Zhuang, W.; Cheng, X.; Ge, W.; Ma, H.; Kong, L.
Abstract : Fusarium head blight (FHB) of wheat is a destructive fungal disease worldwide and has become more severe over the last two decades. Development of FHB resistant wheat varieties is the most effective way to manage FHB. The middle and lower reaches of the Yangtze River are the traditional FHB epidemic areas in China. The landraces and germplasms with resistance to FHB originating from this region were used to identity FHB resistance quantitative trait loci (QTLs). Yangmai 158 and Ningmai 9 are the most popular varieties for commercial wheat production in this region and both have moderate FHB resistance. A high‐density genetic map was constructed using 282 recombinant inbred lines (RILs) from a cross between Ningmai 9 and Yangmai 158. Ten QTLs related to Type II FHB resistance were identified, and QFhb‐3B.1 and QFhb‐5A were stably detected across all environments. Based on position alignment, QFhb‐3B.1 from Ningmai 9 is likely to be Fhb1 and QFhb‐5A from Yangmai 158 is a novel QTL not previously described. A competitive allele‐specific PCR (KASP) marker closely linked to QFhb‐5A was developed and could be used for marker‐assisted selection. Distribution of QFhb‐5A was tested with numerous accessions from a widespread core collection. The results suggest that QFhb‐5A has undergone both natural and artificial selection. Some RILs with both Fhb1 and QFhb‐5A presented better FHB resistance than the parents and could be used in FHB resistance breeding. Abstract : A novel QTL associated with FHB resistance on chromosome 5AL of Yangmai 158 wheat was identified and validated.